2012
DOI: 10.1097/nmc.0b013e318251054e
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Baby-Friendly Practices

Abstract: Breastfeeding is widely viewed as the optimal feeding method for infants among professional nursing and medical organizations. Its health benefits have been comprehensively studied and documented for both infants and mothers. Hospitals and birthing centers can strongly influence the outcomes for mothers who choose to breastfeed by establishing effective breastfeeding behaviors immediately after birth and during the hospital stay. The Baby-Friendly USA initiative outlines 10 steps to successful breastfeeding. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…28 Efforts to conduct newborn assessments and physician rounds at the bedside, among others, have been documented to increase rooming-in, from a rare occurrence, to occurring among 98% of mother-infant dyads in one hospital. 13 …”
Section: | Discussionmentioning
confidence: 99%
“…28 Efforts to conduct newborn assessments and physician rounds at the bedside, among others, have been documented to increase rooming-in, from a rare occurrence, to occurring among 98% of mother-infant dyads in one hospital. 13 …”
Section: | Discussionmentioning
confidence: 99%
“…Often the problems center on resistance to change well-established policy and procedures. 18 Since successful breastfeeding touches almost every policy and procedure in perinatal services as well as the physicians, laboratory personnel, pharmacy, and support staff such as housekeeping, a multidisciplinary leadership team is necessary. 19,20 The place to start is to establish a hospital Baby-Friendly Committee with all of the stakeholders present to direct the process and write or update policy and procedures as necessary.…”
Section: Becoming Baby-friendlymentioning
confidence: 99%
“…21 Often adopting all of the Ten Steps is a process that takes hospitals several years to fully implement. 18 Various approaches are found to work, depending on the area of resistance and depending on whether hospital staff have found creative solutions to road blocks. 22 The Massachusetts Baby-Friendly Collaborative developed 4 recommendations based on its experience: (a) manage expectation of patients, family/friends, and staff with prenatal education and anticipatory guidance; (b) restrict access to materials that can undermine breastfeeding (such as infant formula samples, marketing materials, and use of pacifiers); (c) adopt the appropriate perspectives to creatively implement change, including innovations such as "scripts" for staff to use with patients, standardized assessment tools, and management insight to staff roles such as understanding the time constraints of staffing ratios; and (d) combining BFHI efforts with larger forces by tying state, national, and Joint Commission initiatives to hospital policy changes.…”
Section: Becoming Baby-friendlymentioning
confidence: 99%
“…They found that state policies that support breastfeeding were associated with increased breastfeeding initiation rate in the community and that introducing new breastfeeding laws most likely increased the breastfeeding initiation rate among women . Furthermore, studies have shown that governmental and institutional support through policies and initiatives are some of the key factors for achieving a breastfeeding‐friendly environment and improving breastfeeding practices in health facilities . Our research team examined the barriers and facilitators of breastfeeding practices and found that enforcing breastfeeding support policies could facilitate the implementation of the BFHI in US maternity and birthing hospitals.…”
Section: The 10 Steps To Successful Breastfeedingmentioning
confidence: 96%